1996
DOI: 10.1002/(sici)1520-6807(199610)33:4<285::aid-pits3>3.0.co;2-m
|View full text |Cite
|
Sign up to set email alerts
|

Grade retention among students with learning disabilities

Abstract: This study explored the rates of grade retention among children with undiagnosed learning disabilities. During the 1990–91 school year, data were collected on 344 Michigan students who were referred for special‐education evaluation due to learning problems. Of the 201 students determined to possess a learning disability (LD), 71.6% had been retained at least once before they were referred for special‐education evaluation. Minority and urban LD students were more apt to be retained before being referred for eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(15 citation statements)
references
References 8 publications
1
13
1
Order By: Relevance
“…In absolute terms, the four groups studied here showed rates of scholastic grade failure or special education placement of approximately 30-60%. These proportions are much higher than that of the general population; they are instead comparable to the rates reported for certain clinical samples, such as those with ADHD (19-21% repeat a grade and 25-45% enroll in special education; Biederman et al, 2004;Faraone et al, 1993) or learning disabilities (58-72% repeat a grade; Barnett et al, 1996;McLeskey & Grizzle, 1992). Our previous analyses demonstrated that a contemporary indicator of cognitive ability (performance on an IQ test administered in patients' adulthood) successfully distinguished between groups that differed in their erotic age preferences (Cantor et al, 2004;Cantor, Blanchard, et al, 2005).…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…In absolute terms, the four groups studied here showed rates of scholastic grade failure or special education placement of approximately 30-60%. These proportions are much higher than that of the general population; they are instead comparable to the rates reported for certain clinical samples, such as those with ADHD (19-21% repeat a grade and 25-45% enroll in special education; Biederman et al, 2004;Faraone et al, 1993) or learning disabilities (58-72% repeat a grade; Barnett et al, 1996;McLeskey & Grizzle, 1992). Our previous analyses demonstrated that a contemporary indicator of cognitive ability (performance on an IQ test administered in patients' adulthood) successfully distinguished between groups that differed in their erotic age preferences (Cantor et al, 2004;Cantor, Blanchard, et al, 2005).…”
Section: Discussionmentioning
confidence: 51%
“…These situations are associated with several neurodevelopmentally relevant pathologies, including attention deficit/hyperactivity disorder (ADHD; e.g., Faraone et al, 1993;Place, Wilson, Martin, & Hulsmeier, 2000), learning disabilities (e.g., Barnett, Clarizio, & Payette, 1996;McLeskey & Grizzle, 1992), and premature birth or low birth weight (Buck, Msall, Schisterman, Lyon, & Rogers, 2000;Pinto-Martin et al, 2004), as well as mental retardation. Children may also be assigned to special education systems with diagnoses of conduct disorder or oppositional defiant disorder, which are themselves often comorbid with ADHD (e.g., Déry, Toupin, Pauzé, & Verlaan, 2004;Place et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…The practical implications of these findings for high-risk children and adolescents are very significant. Grade retention has often been used as the first type of intervention for children later diagnosed with learning difficulties or emotional disturbance (Barnett, Clarizio, & Payette, 1996;Mattison, 2000). The present results clearly show that this form of intervention, particularly when used among depressive youth, does not yield the expected benefits.…”
Section: Implications For Research and Interventionmentioning
confidence: 53%
“…It is interesting that in the Special Education Elementary Longitudinal Study, parents reported that significant numbers of students in each disability category had been retained at some point in their educational careers; however, 31% of students with LD had been retained compared to 16% of students with autism (Blackorby, Chorost, Garza, & Guzman, 2005). In addition, two studies (Barnett, Clarizio, & Payette, 1996;McLeskey & Grizzle, 1992) found that 71% and 58% of students with LD, respectively, were retained before being made eligible for special education services. It seems safe to conclude that students with LD are retained at rates higher than their nondisabled peers although it is also clear that more definitive national data are needed.…”
Section: Reading Achievement and Ldmentioning
confidence: 99%